2-Phenyl-tetrahydropyrimidine-4(1H)-ones – cyclic benzaldehyde aminals as precursors for functionalised β2-amino acids - Nahrwold, Markus; Stončius, Arvydas; Penner, Anna; Neumann, Beate; Stammler, Hans-Georg; Sewald, Norbert (Beilstein Journal of Organic Chemistry, 2009)
Novel procedures have been developed to condense benzaldehyde effectively with β-amino acid amides to cyclic benzyl aminals. Double carbamate protection of the heterocycle resulted in fully protected chiral β-alanine derivatives. These serve as universal precursors for the asymmetric synthesis of functionalised β2-amino acids containing acid-labile protected side chains. Diastereoselective alkylation of the tetrahydropyrimidinone is followed by a chemoselective two step degradation of the heterocycle to release the free β2-amino acid. In the course of this study, an L-asparagine derivative was condensed with benzaldehyde and subsequently converted to orthogonally protected (R)-β2-homoaspartate.
Keywords: β2-amino acids; cyclocondensation; diastereoselective alkylation; N,N-acetals; peptidomimetics; ring opening; self-regeneration of stereocentres (SRS)